SCIENTIFIC BASES OF THE OPERATION OF THE DISPERSE PHASE IN ISOTROPIC ELECTRICAL STEEL FORMATION DURING ITS PRODUCTION - Mukhambetov, D.G.; Kurmanaliev, M.B. (Recent Contributions to Physics, 2011)
The physical nature of formation of nanoparticles of the disperse phase in isotropic electrical steel, as a scientific basis of development new and perfection of existing technologies of its production, is considered. Account of a volume fraction of redundant phases is bought at disintegration of a overvibrant solid solution during production of steel. On the basis of the offered model it is received kinetics of coalescence of nanoparticles of the disperse phase at hot rolling. The effect of micro additives of aluminum on coalescence of nanoparticles and on magnetic properties of steel is shown.